Marriage Delay and Economic Rationality: A Socio-Theological Study on Poverty Fear among Young Indonesian Muslims - Puspita, Mega; Rafifatun Nida, Wafiah; Ma’rifah, Latifatul; Hidayah, Ahdiyatul; Fajrin Mima, Nur Luthfiyani (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
The increasing fear of economic instability among young Indonesian Muslims has shifted perceptions of marriage from a theological institution to an economically rational decision. This study critically examines how fear of poverty is constructed through economic rationality and how it directly shapes socio-theological understandings of marriage. Using primary documents such as official statistics and survey reports from BPS, BKKBN, GenRe, and GoodStats, alongside classical and modern Islamic literature on marriage, nafkah, ikhtiyār, and tawakkul, the study employs qualitative content analysis supported by rational choice and modernization theory, interpreted through an Islamic theological lens. Findings demonstrate that economic rationality is now the principal driver of marriage delays, redefining key theological concepts—nafkah, ikhtiyār, and family resilience—in increasingly material terms. The study's main contribution is to clarify the central role of economic fear in young Indonesian Muslims' marriage decisions, integrating economic rationality with Islamic theology. The findings suggest practical strategies to enhance Islamic economic literacy, design integrative premarital education, and inform public policy responsive to modern economic pressures on Muslim families